Marketing-Mix Response Across Retail Formats: The Role of Shopping Trip Types. (March 2020) - Jindal, Pranav; Zhu, Ting; Chintagunta, Pradeep; Dhar, Sanjay
The authors study differences in the effects of prices, nonprice promotions, and brand line length on brand shares at different retail formats. Their conceptual framework rests on the presence of trip-level fixed and category-level variable utility components and shows how the trade-off between these components results in (1) different formats visited on different types of shopping trips and (2) differential marginal sensitivities of brand shares to changes in marketing-mix variables across trip types. Together, these provide predictions on how marketing-mix variables differentially affect brand shares at various retail formats. The authors use Nielsen Homescan and store-level data from 2011–2014 and analyze the top ten spending product categories across four retail formats—convenience stores, drugstores, supermarkets, and mass merchandisers—in over 200 Nielsen markets. Implications for brand manufacturers managing the marketing mix across different formats are offered.JEL codes: M310, L11, D4